Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(\left(2x+7\right)^4=10^{11}:10^7\)
\(\Rightarrow\left(2x+7\right)^4=10^4\)
\(\Rightarrow2x+7=10\)
\(\Rightarrow2x=10-7\)
\(\Rightarrow2x=3\)
\(\Rightarrow x=\dfrac{3}{2}\) hay \(x=1,5\)
b, \(5^{x-1}.7^{x-1}=25.49\)
\(\Rightarrow\)\(5^{x-1}.7^{x-1}=5^2.7^2\)
\(\Rightarrow\left\{{}\begin{matrix}5^{x-1}=5^2\\7^{x-1}=7^2\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}x-1=2\\x-1=2\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}x=3\\x=3\end{matrix}\right.\)
c, \(\left(x-5\right)^{2018}=9.\left(x-5\right)^{2016}\)
\(\Rightarrow\dfrac{\left(x-5\right)^{2018}}{\left(x-5\right)^{2016}}=9.\dfrac{\left(x-5\right)^{2016}}{\left(x-5\right)^{2016}}\)
\(\Rightarrow\left(x-5\right)^2=9\)
\(\Leftrightarrow\left(x-5\right)^2=3^2\)
\(\Rightarrow x-5=3\)
\(\Rightarrow x=3+5\)
\(\Rightarrow x=8\)
1) 3^4.2+2^3.5-7(5^7:5^5)
=3^4.2+2^3.5-7.5^2
=81.2+8.5-7.25
=162+40-175
=202-175=27
2) 5.2^2.2^3-4(5^8:5^6)
=5.4.8-3.5^2
=160-100=60
3) (3^5.3^7):3^10+5.2^4-7^3:7
=3^12:3^10+5.16-7^2
=3^2+80-7^2
=9+80-49=40
4) 15:(3^5:3^4)-2^9:2^7
=15:3-2^2
=5-4=1
5) 5.3^5:(3^8:3^5)-2^3.5
=5.3^5:3^3-8.5
=5.3^2-40
=5.9-40
=45-40=5
( 7200+7199) : 7198 = 7200 : 7198 + 7199 : 7198 = 49 + 7 = 56
( 73+72)x(53+ 56)x ( 33x 3-92) = ( 73+72).(53+ 56) . ( 3^4 - 3^4) = ( 73+72).(53+ 56) . 0 = 0
câu c thì bn xem lại đề nha 23x7x53-( 52x 65+ 52x 35) hay 23x7x53-( 52x 65+ 52 x 35)
(52010 - 52008) : 52008 = 52010 : 52008 - 52008 : 52008 = 52 - 1 = 25 - 1 = 24
(72005 + 72004) : 72004 = 72005 : 72004 + 72004 : 72004 = 7 + 1 = 8
[(52 .23 - 72.2) : 2].6 - 7.25 = (52. 23 : 2 - 72.2:2).6 - 7.25 = (52. 22 - 72).6 - 7.25 = (25.4 - 49).6 - 7. 32 = (100 - 49).6 - 224 = 51.6 - 224 = 306 - 224 = 82
a) \(\left(3^5\times3^7\right):3^{10}+5\times2^4-7^3:7=3^{12}:3^{10}+5\times2^4-7^2\)
\(=3^2-5\times16-7^2=9-80-49=-120\)
b) \(15:\left(3^5:3^4\right)-2^9:2^7=15:3-2^2=5-4=1\)
c)\(5\times3^5:\left(3^8:3^5\right)-2^3\times5=5\times3^5:3^3-2^3\times5\)
\(=5\times3^2-2^3\times5=5\times9-8\times5=45-40=5\)
1 / 5 x 2 2 + ( x + 3 ) = 5 2
20 + ( x + 3 ) = 25
x + 3 = 5
x = 2
2 / 3 2 x 2 + ( x + 25 ) = 10 2
18 + ( x + 25 ) = 100
x + 25 = 82
x = 57
3 / 2 3 x 5 - ( x + 3 2 ) = 10
40 - ( x + 9 ) = 10
x + 9 = 30
x = 21
4 / 7 2 - 7 x ( 13 - x ) = 14
49 - 7 x ( 13 - x ) = 14
7 x ( 13 - x ) = 35
13 - x = 5
x = 8
5 / 14 x - 2 x 7 2 = 2 x 3 x 7
14 x - 98 = 42
14 x = 140
x = 10
1/ 5 x 22 + ( x + 3 ) = 52
2/ 32 x 2 + ( x + 25 ) = 102
3/ 23 x 5 - ( x + 32 ) = 10
4/ 72 - 7 x ( 13 - x ) = 14
5/ 14x - 2 x 72 = 2 x 3 x 7
1 / 5 x 2 2 + ( x + 3 ) = 5 2
20 + ( x + 3 ) = 25
x + 3 = 5
x = 2
2 / 3 2 x 2 + ( x + 25 ) = 10 2
18 + ( x + 25 ) = 100
x + 25 = 82
x = 57
3 / 2 3 x 5 - ( x + 3 2 ) = 10
40 - ( x + 9 ) = 10
x + 9 = 30
x = 21
4 / 7 2 - 7 x ( 13 - x ) = 14
49 - 7 x ( 13 - x ) = 14
7 x ( 13 - x ) = 35
13 - x = 5
x = 8
5 / 14 x - 2 x 7 2 = 2 x 3 x 7
14 x - 98 = 42
14 x = 140
x = 10
nhé !
\(\left(x+2\right)^7=5^7\)
=>x+2=5
=>x=5-2=3
(x+2)^2=5^7
vì 7=7
nên x+2=5
x =7